REPRESENTASI POLA KEPAHLAWANAN DALAM KOMIK TSUKI GA MICHIBIKU ISEKAI DOUCHUU KARYA KEI AZUMI DAN ILUSTRATOR KOTORA KINO - Desi Nopyanti; Hermandra Hermandra; Intan Suri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Joseph Campbell formulated the theory of Hero’s Journey as the stages that a person must pass to be called a her. Based on the Hero’s Journey, the representation of the pattern of heroism in the comic Tsuki ga michibiku isekai douchuu (abbreviated as TGMID) will be written. There are 57 chapters of TGMID comic that will be researched and searched for data that represents the pattern of heroism. This study uses the theory of Joseph Campbell’s Hero’s Journey in his book entitled The hero with a thousand faces (1949). Research shows that Masumi Makoto, who is the main character in the TGMID comic, has experienced and gone through seventeen stages of a hero’s journey. This research is expected to be a reference source for the study of literature, especially for research on Hero’s Journey.Key Words: Hero’s Journey, Tsuki ga Michibiku Isekai Douchuu.